Introduction to maternity and pediatric nursing - Leifer, Gloria (St. Louis, Mo. : Elsevier/Saunders, 2011)
Introduction to Maternity and Pediatric Nursing provides a solid foundation in obstetrics and pediatric nursing. An easy-to-follow organization by developmental stages, discussion of disorders by body system from simple-to-complex and health-to-illness, and a focus on family health make it a complete guide to caring for maternity and pediatric patients. --from publisher description.
Unit 1: Overview Of Maternity And Pediatric Nursing: United States Unit 2: Maternal-Newborn Nursing And Women's Health 10: Nursing care of women with complications after birth: Unit 3: Growing Child And Family: Unit 4: Adapting Care To The Pediatric Patient: 22: Health care adaptations for the child and family: Unit 5: Child Needing Nursing Care: Unit 6: Changing Health Care Environment
Includes bibliographical references and index.
Keywords: Maternity nursing; Pediatric nursing; Maternal-Child Nursing -- methods; Pediatric Nursing -- methods